2021
DOI: 10.1371/journal.pone.0251361
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality, molecular epidemiology, and virulence of Respiratory Syncytial Virus (RSV): A perspective into the Brazilian Influenza Surveillance Program

Abstract: Background Respiratory Syncytial Virus (RSV) is the main cause of pediatric morbidity and mortality. The complex evolution of RSV creates a need for worldwide surveillance, which may assist in the understanding of multiple viral aspects. Objectives This study aimed to investigate RSV features under the Brazilian Influenza Surveillance Program, evaluating the role of viral load and genetic diversity in disease severity and the influence of climatic factors in viral seasonality. Methodology We have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 54 publications
4
16
0
Order By: Relevance
“…The Northern region did not experience a distinct RSV season but had ongoing RSV activity throughout the year. Previous studies have shown RSV seasonality in tropical regions to be diverse, 4,5 with some tropical regions such as Brazil and Thailand experiencing distinct RSV seasons, 4,21 while others such as Cote D'Ivoire had no observed seasonality 4 . The Northern Territory of Australia, a tropical region adjacent to the Northern region of WA, has reported a distinct RSV season in their rainy season 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The Northern region did not experience a distinct RSV season but had ongoing RSV activity throughout the year. Previous studies have shown RSV seasonality in tropical regions to be diverse, 4,5 with some tropical regions such as Brazil and Thailand experiencing distinct RSV seasons, 4,21 while others such as Cote D'Ivoire had no observed seasonality 4 . The Northern Territory of Australia, a tropical region adjacent to the Northern region of WA, has reported a distinct RSV season in their rainy season 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Senegal described a 3.4% coinfection rate with both subgroups, 33 while another report from Brazil found 1.4% of codetections. 31 Generally, dual infections occur rarely in HRSVpositive respiratory samples. 34 The data we gathered from this study consolidate what we found previously, 13 that cough was most likely related to clinical symptoms of HRSV infection rather than fever (84%; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The quantum of direct cytopathic effects exerted by RSV on respiratory epithelium might depend on the viral load (4), however, it is still under speculation because of contradictory findings (5)(6)(7). The Th1 cytokines are needed for viral clearance but an overwhelming secretion of pro-inflammatory cytokines like IL-6 and TNFα cause recruitment of neutrophils that damage the respiratory epithelium (8).…”
Section: Text Introductionmentioning
confidence: 99%
“…Positive correlation of TNFα & IL-10 (r = 0.464, p <0.001), TNFα & IL-6 (r= 0.360, p <0.001), TNFα & MMP-9 (r =0.208, p <0.05) and IL-10 & IL-6 (r = 0.468 p <0.001) cytokines and inverse correlation of MMP-9 & IFN-Ƴ (r = -0.352, p <0.01) was observed with severe ALRTI patients.DiscussionAn early recognition of disease progression, based on specific biomarkers rather than subjective scoring systems, is imperative to decrease the morbidity and mortality associated with RSV. The association of viral load with disease severity remained controversial (25-27).Haddadin et al 2020(5) and Cruz et al 2020(6) have reported a positive correlation with disease severity whereas Vianna et al 2021(7) documented that viral load had no relation with severity of disease. Our data suggested that viral load does not have any significant variation with the age or requirement for intensive care management, however, it was a marker for transition from non-severe to severe ALRTI.…”
mentioning
confidence: 99%